An Intersectional Feminist Reading of Bapsi Sidhwa's Water - Numaira Hamid Khan (University of Chitral Journal of Linguistics and Literature, 2020)
Intersectionality has been recognized and widely taken by interdisciplinary fields that include Cultural studies, American studies, and Media studies to demonstrate a range of social issues. It focuses on the experiences of people in a different social and political context. The intersectional framework confronts significant social division axes that include race, class, gender, and disability that function together and influence each other. These social axes operate the power structures of a particular society that can cause inequality and discrimination. In literary studies, women representation is no more confined to European and American academic writings. Within the feminist framework, the South Asian fiction writers also demonstrate a feminist approach in their works. Pakistani authors have indicated religion's exploitation as one of the central intersectional tropes in their literary work. Bapsi Sidhwa's is one of the prominent feminist voices from Pakistan in diasporic English Literature. One of her novels, Water (2006), is based on Deepa Mehta's award-winning film, explores the life of the marginal and subaltern Hindu widows in India. The novel provides an insight into the intersectional nature of the Indian Hindu widows in a patriarchal society of a subcontinent where different power domains hold and impose dominant hierarchies. The paper's objective is to highlight the intersection of religion, gender, caste and politics against the backdrop of the Indian anti-colonial movement. It shows how power relations can manipulate cultural norms and use religion as a powerful tool to establish its hegemonic control over these marginalized widows who suffer as silent victims.